2014
DOI: 10.1371/journal.pone.0113876
|View full text |Cite
|
Sign up to set email alerts
|

Association of Residual Plasma Viremia and Intima-Media Thickness in Antiretroviral-Treated Patients with Controlled Human Immunodeficiency Virus Infection

Abstract: BackgroundWhile residual plasma viremia is commonly observed in HIV-infected patients undergoing antiretroviral treatment (ART), little is known about its subclinical consequences.MethodsThis cross-sectional study included 47 male, never-smoking, non-diabetic patients with ≥4 years of ART and controlled HIV-replication (HIV-viral load, VL <20 copies/mL for ≥1 year). Residual HIV-VL was measured using an ultrasensitive assay (quantification limit: 1 copy/ml). Patients were categorized as having detectable (D; 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…While a recent AIDS Clinical Trials Group study (A5321) did not find a correlation between residual viral replication (using single-copy assays) and residual inflammation, this analysis focused on a highly selected cohort of participants who had long-standing viral suppression (median, 7 years) and were originally enrolled in clinical trials [ 49 ]. In comparison, other studies in different cohorts have identified associations of residual viremia and HIV-DNA with inflammation [ 14 , 50 , 51 ] and with increased cardiovascular morbidity [ 26 , 27 ]. Given the well-established association between residual inflammation and morbidity/mortality in HIV [ 24 , 25 ], it remains plausible that suboptimal ART adherence could trigger episodes of residual HIV replication and heightened inflammation that result in adverse non-AIDS clinical outcomes despite virologic suppression in plasma.…”
Section: Discussionmentioning
confidence: 95%
“…While a recent AIDS Clinical Trials Group study (A5321) did not find a correlation between residual viral replication (using single-copy assays) and residual inflammation, this analysis focused on a highly selected cohort of participants who had long-standing viral suppression (median, 7 years) and were originally enrolled in clinical trials [ 49 ]. In comparison, other studies in different cohorts have identified associations of residual viremia and HIV-DNA with inflammation [ 14 , 50 , 51 ] and with increased cardiovascular morbidity [ 26 , 27 ]. Given the well-established association between residual inflammation and morbidity/mortality in HIV [ 24 , 25 ], it remains plausible that suboptimal ART adherence could trigger episodes of residual HIV replication and heightened inflammation that result in adverse non-AIDS clinical outcomes despite virologic suppression in plasma.…”
Section: Discussionmentioning
confidence: 95%
“…As persistent residual viremia appears to impact immune activation, inflammation, and microbial translocation [24, 25], VLs at ultralow levels could bear some clinical importance. The ongoing presence of virus despite low viral concentrations could prevent some systemic inflammatory markers from returning to normal levels; however, the association between residual inflammation and residual HIV-1 replication is probably bi-directional and complex [26].…”
Section: Discussionmentioning
confidence: 99%
“…Higher progression in carotid intima-media thickness was present in individuals with persistent non-suppressed viremia (>400 copies/mL) in a United States study [ 30 ]. Furthermore, persons with residual viremia (detectable VL < 20 copies/mL) had higher carotid intima-media thickness than those with undetectable VL in a French cross-sectional study [ 31 ]. However, in Brazilian PWH, higher cumulative exposure to viremia, measured as viremia-copy-years, was not associated with carotid intima-media thickness after adjustment for traditional risk factors such as smoking, body mass index, family history of CVD, and hypertension [ 32 ].…”
Section: Discussionmentioning
confidence: 99%